Qibla Direction Determination in Historical Mosques: Methodological and Accuracy Assessment at Al-Anwar Grand Mosque, Bandar Lampung - Khairunnisa, Ariba; Muhammad Adam; Rivaldi, Muhammad Haikal; Zain, Muhammad Fajri Kholili (Al-Hilal: Journal of Islamic Astronomy, 2025)
Qibla direction in mosques, historically, was determined using simple methods and traditional tools, resulting in relatively low accuracy. This study aims to analyze the methods and precision of Qibla direction at Jami’ Al-Anwar Mosque, Bandar Lampung, using a qualitative field approach supported by modern instruments. The findings indicate that the true Qibla direction is 295° 18′ 25.82″, while the mosque’s current orientation measured with a theodolite is 295° 12′ 10″ and with a mizwala instrument is 295° 12′ 13.82″. The difference of only 0° 6′ 15.82″ classifies the mosque’s Qibla as accurate according to deviation tolerance theory. Contributing factors include the use of an istiwā’ stick to determine cardinal directions, advances in scientific knowledge, and religious motivations to ensure precision. These results highlight the significance of combining traditional techniques and modern technology to maintain the accuracy of Qibla orientation in historic mosques.